2020
DOI: 10.1038/s41598-020-77791-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of comorbid asthma on severity of coronavirus disease (COVID-19)

Abstract: The severity of the coronavirus disease (COVID-19) is associated with various comorbidities. However, no studies have yet demonstrated the potential risk of respiratory failure and mortality in COVID-19 patients with pre-existing asthma. We selected 7272 adult COVID-19 patients from the Korean Health Insurance Review and Assessment COVID-19 database for this nationwide retrospective cohort study. Among these, 686 patients with asthma were assessed by their severities and evaluated by the clinical outcome of CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
1
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 50 publications
4
66
1
6
Order By: Relevance
“…By contrast, Lee et al [ 99 ] found that, although asthma was not a risk factor for poor prognosis, higher mortality was observed among those who had experienced an acute exacerbation during the previous year. Similarly, Choi et al [ 100 ] reported that a pre-existing diagnosis of asthma was associated with poor outcomes among those with COVID-19, although asthma severity and the use of asthma medications were not independent risk factors.…”
Section: Covid-19 In Patients With Eosinophil-associated Diseases Andmentioning
confidence: 94%
“…By contrast, Lee et al [ 99 ] found that, although asthma was not a risk factor for poor prognosis, higher mortality was observed among those who had experienced an acute exacerbation during the previous year. Similarly, Choi et al [ 100 ] reported that a pre-existing diagnosis of asthma was associated with poor outcomes among those with COVID-19, although asthma severity and the use of asthma medications were not independent risk factors.…”
Section: Covid-19 In Patients With Eosinophil-associated Diseases Andmentioning
confidence: 94%
“…Les principaux facteurs associés à la létalité du COVID-19 sont résumés dans le Tableau 1 , qui reprend des données issues d’études différentes en dehors de toute vaccination, citées en références ( Tableau 1 ) [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] .…”
Section: Quels Patients De Pneumologie Sont à Risque De Covid-19 Grave ?unclassified
“…Asthma was not a significant risk factor for respiratory failure or mortality among all COVID-19 patients. However, a history of acute exacerbation (OR = 2.63, p = 0.043) was a significant risk factor for death among COVID-19 patients with asthma [64]. In anotherstudy, asthma severity was not an independent factor for poor clinical outcomes of COVID-19, but patients with step 5 asthma had a prolonged in-hospital stay duration than those with step 1 asthma in both univariate and multivariate analyses [65].…”
Section: Severe Asthma and Covid-19mentioning
confidence: 89%